Environmentally focused cooperation projects as a stimulus for the development of old industrialised regions. Case studies in eastern German regions in which small and medium-sized towns predominate - Holger Leimbrock; Gerd Lintz (European Regional Science Association (ERSA), 2002)
Large parts of eastern Germany are displaying symptoms typical of old industrialised regions. Regions finding it particularly hard to adapt are those in which small and medium-sized towns predominate and which therefore only have limited administrative and financial assets as a rule. Alongside more traditional forms of regional development such as, for instance, the setting-up of industrial estates by local authorities and the enhancement of transport infrastructure, a number of interesting and more novel approaches have been adopted here. The development strategies examined in the present article have three distinguishing features. Firstly, they are explicitly environmentally focused. Secondly, they are co-operative in nature and can involve a multitude of actors. Thirdly, the relevant projects call for mutual exertion over a limited period of time in order to fulfil a strategic objective that is distinctly out of the ordinary, hence justifying the "major project" tag. To determine whether such projects can actually provide a stimulus for the development of the regions under review as well as what sort of factors their success may depend on, three specimen cases are being investigated that differ from one another in terms of both project type and regional characteristics. The first case study concerns what became the Saxony-Anhalt correspondence region for the EXPO 2000 event in Hanover, which ran under the slogan "Mankind - Nature - Technology". This project in a region defined by the medium-sized towns of Dessau, Bitterfeld, Wolfen and Wittenberg has strong organisational affinities with the Emscher Park International Building Exhibition (IBA), which was held in the Ruhr Area conurbation and is still having a big impact on the debate concerning strategies of regional development. The second example involves a predominantly small-town region in the eastern Ore Mountains in which the Model-Urban-Ecology Planning Game was played. The aim of the planning game was to identify the level of urban ecology that can be put to effect with any success from an intermunicipal perspective. The third case study is the Green Ring around Leipzig. The key emphasis here is on co-operation to the good of landscape development between the region around Leipzig, an area in which small towns still predominate, and the city itself. Viewed in their entirety, all three environmentally focused co-operation projects are having a considerable impact on regional development. In different ways, it has proved possible not only to improve the situation regarding the environment and the environmental awareness of the actors involved but also to mobilise and educate them in matters of regional co-operation to a degree that exceeds the scope of the actual project. One factor with a crucial bearing on the outcome is the crystallisation of a certain "state of emergency" in a region by dint of the special nature of the undertaking, the limited term of the project, financial backing from outside parties and greater awareness from further afield. Keywords: Co-operation of actors, environmental policy, project oriented planning, regional development
Keywords: 330